b - Suzuki, Nobuo (Tuttle Publishing, 2020)
Wabi Sabi is a Japanese Zen philosophy that embraces the idea that all things are imperfect, incomplete, and transient.
Includes bibliographical references.
Keywords: Aesthetics, Japanese; Conduct of life; Philosophy, Japanese